Factors Affecting the Adoption and use of NERICA Varieties among Rice Producing Households in Ghana - Asante, B.O.; Wiredu, A.N.; Dogbe, W.; Asuming-Boakye, A.; Frimpong, B.N.; Haleegoah, J.; Nortey, J.; Diagne, A. (2013)
This paper uses cross sectional data which were collected from 200 smallholder rice producers in Ghana, to examine the factors influencing the adoption and extent of use of NERICA rice varieties in Ghana. About 57.93 per cent of the sampled rice producers allocated 35.77 per cent of their land to NERICA accounting for about 33.13 per cent of seeds planted. The Tobit regression model suggests fertilizer use, existence of other complementary projects in the area, proportion of active persons in household, access to alternative income sources, distance to seed source and education as key factors influencing the quantity of seeds planted as well as the proportion of land allocated to the NERICA varieties. With the exception of distance to seed source, all the other factors positively influenced the extents of adoption. The findings suggest the need to ensure availability of NERICA seeds within acceptable distances to farming communities. This could be achieved through identification of certified rice seed growers in strategic locations throughout the country and supported with necessary logistics to produce NERICA seeds at reasonable proximities to rice producing communities. This could also be enhanced through establishment of linkages with existing institutions and projects to compliment promotional efforts.